Performance Evaluation of Spindle Type Cotton Picker - Prasad, J; Kapur, Tarun; Sandhar, N S; Majumdar, N; Patil, P G; Shukla, S K; Jaiswal, B N; Patil, A B (Journal of Agricultural Engineering, 2007)
Entire cotton picking in India is manual. It is not only a slow process but involves extremely tedious hard work. Due to impending scarcity of labour, mechanization of cotton harvesting is considered to be of vital importance. A study was conducted on the performance of a two-row self-propelled cotton picker at different locations in India. The performance of John Deere 9935 cotton picker was evaluated at PAU Ludhiana and CICR, Nagpur. Tests at PAU, Ludhiana was conducted on LH 1556 having average plant height of 112.9 cm. The mean values of forward speed, effective field capacity, total harvesting loss, mechanical picking efficiency and picker efficiency were 2.62 km/h, 0.28 ha/h, 23.62 %, 75.7 % and 76.4 %, respectively. The field evaluation of cotton picker at CICR, Nagpur was conducted on seven varieties/genotypes, namely CNH 120 MB, CNH 123, CNH 155, CNH 911, CNH 2713, CNH 4736 and GSH 2. The average height of plant and lowermost boll were 85.9 cm, 86.0 cm, 98.1 cm, 81.9 cm, 73.2 cm, 77.8 cm and 86.3 cm and 9.0 cm, 10.9 cm, 21.6 cm, 11.6 cm, 16.4 cm and 12.3 cm for CNH 120 MB, CNH 123, CNH 155, CNH 911, CNH 2713, CNH 4736 and GSH 2, respectively. The mean values of forward speed, effective field capacity, fuel consumption, total harvesting loss, mechanical picking efficiency and picker efficiency were 2.20-3.38 km/h, 0.278-0.563 ha/h, 22.0 - 24.0 I/h, 14.29-31.74 %, 55.6 - 83.1 % and 68.3-85.7 %, respectively. The cultural practices and staggered blooming characteristics of present Indian cotton varieties poses challenge to engineers in mechanization of cotton picking. With the advent of new genotypes, it may be possible to introduce mechanical cotton pickers successfully.